The use of coronary CT angiography for the evaluation of chest pain - Schlett, Christopher L.; Pursnani, Amit; Marcus, Roy P.; Truong, Quynh A.; Hoffmann, Udo (Cardiology in review, 2014)
Coronary computed tomography angiography (CCTA) may improve the diagnosis and management of acute and stable chest pain syndromes. The key for caregivers of patients presenting with acute chest pain is the early identification and management of life-threatening conditions, such as acute coronary syndromes, pulmonary embolism, and acute aortic dissection. The main goal in stable chest pain syndromes is to determine the extent and severity of coronary artery disease. This review article will critically evaluate the current literature supporting the evidence for the clinical use of CCTA in acute and stable chest pain syndromes, considering the latest innovations in CCTA technology and their potential impact on patient care.